Male microbiota-associated metabolite restores macrophage efferocytosis in female lupus-prone mice via activation of PPARγ/LXR signaling pathways. Issue 1 (10th January 2023) - Harder, James W; Ma, Jing; Alard, Pascale; Sokoloski, Kevin J; Mathiowitz, Edith; Furtado, Stacia; Egilmez, Nejat K; Kosiewicz, Michele M
Abstract: Systemic lupus erythematosus development is influenced by both sex and the gut microbiota. Metabolite production is a major mechanism by which the gut microbiota influences the immune system, and we have previously found differences in the fecal metabolomic profiles of lupus-prone female and lupus-resistant male BWF1 mice. Here we determine how sex and microbiota metabolite production may interact to affect lupus. Transcriptomic analysis of female and male splenocytes showed genes that promote phagocytosis were upregulated in BWF1 male mice. Because patients with systemic lupus erythematosus exhibit defects in macrophage-mediated phagocytosis of apoptotic cells (efferocytosis), we compared splenic macrophage efferocytosis in vitro between female and male BWF1 mice. Macrophage efferocytosis was deficient in female compared to male BWF1 mice but could be restored by feeding male microbiota. Further transcriptomic analysis of the genes upregulated in male BWF1 mice revealed enrichment of genes stimulated by PPARγ and LXR signaling. Our previous fecal metabolomics analyses identified metabolites in male BWF1 mice that can activate PPARγ and LXR signaling and identified one in particular, phytanic acid, that is a very potent agonist. We show here that treatment of female BWF1 splenic macrophages with phytanic acid restores efferocytic activity via activation of the PPARγ and LXR signaling pathways. Furthermore, we found phytanic acid may restore female BWF1 macrophage efferocytosis through upregulation of the proefferocytic gene CD36. Taken together, our data indicate that metabolites produced by BWF1 male microbiota can enhance macrophage efferocytosis and, through this mechanism, could potentially influence lupus progression. Abstract : A male microbiota-associated metabolite activates signaling through LXR/RXR and PPARγ/RXR heterodimers, upregulating expression of proefferocytic genes and enhancing efferocytosis in macrophages from female lupus-prone mice.